Secondary Metabolites from Aquilaria subintegra Leaves and their Radical Scavenging Activity - Mastura Ibrahim (Tanjung Malim, 2023)
Secondary Metabolites from Aquilaria subintegra Leaves and their Radical Scavenging Activity by Mastura Ibrahim